Comparative analysis of pathways to early intervention services and duration of untreated psychosis in two Canadian cities. Issue 6 (9th March 2016) - Flora, Nina; Anderson, Kelly K.; Ferrari, Manuela; Tuck, Andrew; Archie, Suzanne; Kidd, Sean; McKenzie, Kwame; ,
Abstract: Aim: Understanding pathways to early intervention services for psychosis in the local context is crucial, as the structure and organization of services need to be considered. This study compared pathways to early intervention services in two Canadian cities. Methods: Data on pathways to care and duration of untreated psychosis were collected from 171 people admitted to early intervention services in Toronto ( n  = 150) and Hamilton ( n  = 21). We compared the cities on several indicators of pathway to care and duration of untreated psychosis. Results: Pathways to care were more complex in Toronto, where people saw a greater number of health care services (median = 6, interquartile range = 3–9) than those in Hamilton (median = 3, IQR = 1–4). General practitioner involvement was higher in Toronto (56.0% vs. 33.3%). We did not find differences in the median duration of untreated psychosis. Conclusions: Pathways to early intervention services could be streamlined, and general practitioners may be a target for strategies to improve pathways to care.